Pengaruh Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada CV. Dewi Lestari - Adi Putra Prasetya; Bangun Putra Prasetya (STIKes Ibnu Sina Ajibarang, 2024)
The purpose of this research is to look at how Cv. Dewi Lestari fares when given different levels of incentive and punishment for their task. A quantitative descriptive strategy is used to gather data through the distribution of questionnaires to a total of 20 respondents. Statistical analysis using multiple linear regression tests is thus employed for data analysis. Employee performance at Cv. Dewi Lestari is influenced by both intrinsic and extrinsic factors, according to this study's findings. Both the F-test and the t-test, which are partial tests, found statistically significant values for the two independent variables, lending credence to the hypothesis. Thus, this study's results show that the Cv. Dewi Lestari's performance is affected by both intrinsic drive and external work discipline.